Study of the physical and mechanical properties of capirona (Calycophyllum spruceanum [Bentham] Hooker f. ex Schumann) wood as a potential for solid wood flooring production - Egoavil Cueva Gálvez, Graciela Isabel (2023)
The present study aimed to determine the physical and mechanical properties of a 20-year-old plantation of the species Calycophyllum spruceanum, known in Peru as “capirona,” for its potential for wood flooring production. For this purpose, samples were collected from six trees in a plantation located in the district of Curimaná, department of Ucayali, Peru. Physical and mechanical property tests were conducted following the American Society for Testing and Materials (ASTM) D143-94(2000) standard. The results showed that capirona has a basic density of 0,68 g/cm3, which is considered a heavy wood, and exhibits moderate dimensional stability. The mechanical properties demonstrated that the wood has a high resistance to bending and compression parallel to the grain, and a very high resistance to compression perpendicular to the grain, hardness, shear, and toughness. Based on the Peruvian Technical Standard (NTP) 251.135:2013, the characteristics of capirona wood for flooring were evaluated, yielding positive results and indicating its potential for solid wood flooring production.